PENGARUH PENDAPATAN, LITERASI KEUANGAN DAN SIKAP KEUANGAN TERHADAP PERENCANAAN KEUANGAN - Ranat Mulia Pardede; Paradina Fussilat; Ahmad Yani; Yuritanto, Yuritanto (Juremi: Jurnal Riset Ekonomi, 2024)
This research aims to determine the influence of income, financial literacy and financial attitudes on the financial planning of accounting students at STIE Pembangunan Tanjungpinang, both simultaneously and partially. The method used in this research is a quantitative method. This research uses primary data. Data collection techniques use offline/class questionnaires and literature studies. Data analysis by conducting data quality tests (validity and reliability), classical assumption tests (normality, multicollinearity and heteroscedasticity), multiple linear regression analysis, hypothesis testing (t test and f test) and coefficient of determination test. The research results show that the income and financial literacy variables have no partial effect on financial planning, while the financial attitude variable has a partial effect on financial planning. However, this research also shows that the variables income, financial literacy and financial attitudes have a simultaneous influence